Creating a learning school - Middlewood, David (Paul Chapman, 2005)
"Creating a Learning School" gives a complete overview of how schools can adapt to meet changing needs. They look at the teacher as learner, learning outside the classroom, and the nature of leadership in learning schools, and provide practical solutions to the problems of staffing, resourcing and assessment.